Cross-linked PEDOT: PSS as an alternative for low-cost solution-processed electronic devices - Colucci, Renan [UNESP]; Quadros, Matheus Henrique [UNESP]; Feres, Flávio Henrique [UNESP]; Maia, Francisco Barbosa; de Vicente, Fábio Simões [UNESP]; Faria, Gregório Couto; Santos, Lucas Fugikawa [UNESP]; Gozzi, Giovani [UNESP] (Elsevier, 2018)
A number of solution-processed electronic materials have been developed for application in printed devices, which are normally built by piling up several coated layers one on the top of the other. To achieve low-cost and simple to manufacture printed devices, stable and easy to process layers are mandatory. Here we introduce a mixture of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) with 3-glycidoxypropyltrimethoxysilane (GPTMS) as solution-processed material that becomes insoluble in water after film processing. We performed morphological, optical and electrical characterization in the proposed composite and highlight its advantages as a stable transparent electrode in light-emitting diodes as well as in electrochromic devices.
Keywords: Cross-linked PEDOT:PSS; Hybrid light-emitting diodes.; Organic electrochromic devices; Organic semi-transparent electrodes